2007
DOI: 10.1021/ac061414z
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Enzymatic Optical Biosensors Using Mass Transport Limiting Nanofilms. 1. Fabrication and Characterization Using Glucose as a Model Analyte

Abstract: Abstract"Smart tattoo" sensors -fluorescent microspheres which can be implanted intradermally and interrogated noninvasively using light -are being developed as potential tools for in vivo biochemical monitoring. In this work, a platform for enzymatic tattoo-type sensors is described, and prototype devices evaluated using glucose as a model analyte. Sensor particles were prepared by immobilizing Pt(II) octaethylporphine (PtOEP), a phosphorescent dye readily quenched by molecular oxygen, into hybrid silicate mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 54 publications
3
102
0
Order By: Relevance
“…[13][14][15] Demonstrations of potential hydrogel sensor formats over the years have included poly(ethylene glycol)-based microspheres and fibers [13][14][15] and includes a variety of hollow polymeric capsules and various nanocomposite particulate systems using other encapsulating materials. [16][17][18][19][20] Utilizing these unique properties of hydrogels in a fully implantable CGM may circumvent repetitive tissue trauma and infection associated with the percutaneous nature of traditional CGM devices in vivo. 9,21 Used in medical devices for decades, one of the most widely studied and well-characterized hydrogels for biomedical applications is poly (2-hydroxyethyl methacrylate) (pHEMA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Demonstrations of potential hydrogel sensor formats over the years have included poly(ethylene glycol)-based microspheres and fibers [13][14][15] and includes a variety of hollow polymeric capsules and various nanocomposite particulate systems using other encapsulating materials. [16][17][18][19][20] Utilizing these unique properties of hydrogels in a fully implantable CGM may circumvent repetitive tissue trauma and infection associated with the percutaneous nature of traditional CGM devices in vivo. 9,21 Used in medical devices for decades, one of the most widely studied and well-characterized hydrogels for biomedical applications is poly (2-hydroxyethyl methacrylate) (pHEMA).…”
mentioning
confidence: 99%
“…Sensor response depends on the availability of the substrates glucose and oxygen to the enzyme (governed by mass transport) as well as the affinity of the enzyme for both substrates. 16,19,20,26,27 We have previously shown that pHEMA-based hydrogels can be functionalized with enzymes and long-lifetime phosphors to be used as luminescence-based glucose sensors. In the same study, we illustrated the ability to tune sensor behavior through hydrogel composition by influencing glucose and oxygen diffusion.…”
mentioning
confidence: 99%
“…Enzymatic biosensor, introduced by Clark and Lyons when they built the first glucose biosensor in 1962 (Clark and Lyons, 1962), is a very popular field in bioanalytical applications witnessing tremendous work done over the past 50 years (Odaci et al, 2009;Stein et al, 2007;Wilson and Turner, 1992). Enzymes are the most used biocatalytic elements enabling the detection of analytes in various ways, such as measuring the consumed or produced species after the enzymatic reactions (Gough et al, 1985;Guilbault and Lubrano, 1973;Reach and Wilson, 1992) or tracking the electrons passed through the electrodes during reactions (Holland et al, 2011;Shan et al, 2009;Si et al, 2011;Wang, 2008).…”
Section: Molecular Targets and Biomarker Sensingmentioning
confidence: 99%
“…[14,15] We applied the Layer-by-Layer (LbL) self-assembly technique for nanofilm construction, due to the flexibility of the approach to create composite films with nanometer resolution. [16][17][18][19][20] Recently, a series of reports described the transport of various molecular species through polyelectrolyte multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Exploiting this extraordinarily low glucose diffusivity and precision for assembly, we showed that LbL films can be applied as tunable diffusion-limiting coatings for optical biosensors. [14,15] To further make sensors appropriate for in vivo deployment, it is essential to create an interface with the biological system that minimizes the response to the foreign material, such as inflammation and immune system attack. Protein adsorption is the initial event that mediates host response to foreign materials.…”
Section: Introductionmentioning
confidence: 99%